HLA and malaria in four colombian ethnic groups - Marcos Restrepo; William Rojas; Fabiola Montoya; Asirid E. Montoya; Deborah V. Dawson (Revista do Instituto de Medicina Tropical de São Paulo, 1988)
HLA antigens and their relationship with malaria infection were studied in four different ethnic groups in Colombia (South America): two groups of indians (Kunas and Katios), one of negroes and a group of mixed ancestry. A total of 965 persons were studied, 415 with malaria and 550 as controls. HLA-A,B, and C antigen frequencies in the four groups are reported. The association of each HLA antigen with malaria infection due to P. vivax and to P. falciparum was evaluated. Negroes, Kunas and Katios indians variously lack from 6 to 9 of the HLA antigens found in the mixed group. In the designated ethnic groups, antigens B5, B13, B15, Cw2 and Cw4 showed borderline association with malaria infection. However, in the mixed ethnic group, statistically significant associations were found with malaria infection and the presence of A9, Aw19, B17, B35, and Z98 (a B21-B45: crossreacting determinant) with few differences when P. vivax infection and P. falciparum infection were considered individually. This finding may represent a lack of general resistance to malaria in the group that harbors antigens of Caucasian origin. These individuals have been in direct and permanent contact with malaria only in the past 65 years. In contrast, indians, both Kunas and Katios, and Negroes have lived for centuries in malaria endemic areas, and it is possible that a natural selection system has developed through which only those individuals able to initiate an acute immune response to malaria have survived.